Characterization of CoNi-Sn catalyst for autothermal reforming of methane - Songip, A. R.; Nasri, N. S.; Kusworo, T. D.; Ismail, S. R. (2004)
Hydrogen can be produced from natuml gas through autothermal reforming process (ATR). ATR is a combination of steam reforming and partial oxidation process. CoNiSn with different catalyst supports e.g. MgO and AI2O3 has been chose to be used on this autothermal refonning of methane (ATR). Temperature Programmed Reduction (TPR) and X-ray Diffraction (XRD) have been done to study the bulk structure of the catalyst. From the TPR and XRD. the addition of tin into MgO-supported catalyst will become as anti coking agent as it will react with carbide, since it deposited at the outer laycr of the matrix CoO-Ni0-Mg0 solid solution phase.